Laparoscopic transvesical vesicovaginal fistula repair with the least invasive way: Only three trocars and a limited posterior cystotomy - Giannakopoulos, Stilianos (Asian J Urol, 2020)
OBJECTIVE: Two conventional approaches for vesicovaginal fistula (VVF) repair are transabdominal repair for supratrigonal VVF and transvaginal approach for low lying fistulae. Laparoscopic surgery was introduced to duplicate the surgical steps of the transabdominal approach with reduction in morbidity. We report a series of patients treated with a modified laparoscopic technique which includes the use of only three trocars and a limited posterior cystotomy. METHODS: We retrospectively reviewed the data of eight patients who underwent laparoscopic VVF repair with our standardized technique from January 2015 to April 2018. Only cases with a supratrigonal fistula were included. We constantly used only three trocars. A limited 2 cm midline posterior cystotomy was performed using ultrasonic energy. A stay suture on a straight needle was passed percutaneously in the abdomen, then on either side of the cystotomy and finally was exteriorized to maintain countertraction. The cystotomy was extended downwards to include the fistula site. The fistula was dissected circumferentially to raise the bladder and vaginal flaps. The vaginal defect was closed in a transverse fashion and the cystotomy was closed vertically. RESULTS: Mean operative time was 178±31.6 min and estimated blood loss was 60±18.7 mL. Flap interposition was performed in six cases. No intraoperative complications were recorded. Mean hospital stay was 2.25±0.89 days. During hospitalization two patients experienced postoperative complications (Clavien grade I). Mean follow-up was 20.9±11.1 months (6.0–39.0 months). All patients remained continent during the follow-up period. CONCLUSIONS: This minimally invasive laparoscopic approach with only three trocars and limited posterior cystotomy provides excellent results with minimum morbidity.